Exostructure services for infrastructure resources optimization - JosephNg, P.S. (Universiti Teknikal Malaysia Melaka, 2016)
The emerging challenges for Malaysia medium sized enterprises to remain competitive is testing and stressing the extent of the capacity and even the capability of IT infrastructure, especially regarding on its resource utilization for cost effective sustainability during this time of economic uncertainty. They are stuck in between the larger enterprises that enjoy economies of scales and the much smaller enterprises with insufficient baseline to motivate contribution. This research evaluated two theories from Harvard University: Commodity of IT infrastructure and Disruptive Technology for its suitability and ascertain its adaptability to a localized environment. Primary data collection via mass survey is conducted for exploratory analysis. The findings show significant imbalance IT infrastructure investment decision and the reasons behind, supported by the statistical evidences collected. The paper then seeks to establish a new cost effective virtualization framework for them to plan ahead. As infrastructure investment requires a longer period to yield positive contribution, early implementation will prepare them for the next bull run.